Effect of urban waste composted with rock phosphate on nodulation, growth and P absorption in beans - Peixoto, Ricardo Trippia dos G.; Franco, Avilio Antonio; Almeida, Dejair Lopes de (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment with a clayey Red-Yellow Latosol was conducted to study the effect of urban waste, composted in heaps in the open field with several phosphate sources, on nodulation, growth and P accumulation of Phaseolus vulgaris L. The experimental design was a factorial 3 x 12 randomized in blocks with four replications, with three levels of pH (4.8,5.3 and 6.1 in water) and twelve treatments. The P sources used were rock phosphates from Patos de Minas and Araxá, MG, Brazil, and triple superphosphate (TS), that were added to the soil with and without compost, and after had been composted. The seeds were inoculated with a mixture of Rhizobium phaseoli strains COS and SEMIA 487. The results showed a beneficial effect of the compost on nodulation, N and P accumulation in the plants and ameliorated the detrimental effect of soil acidity. However the addition of Patos de Minas or Araxá rock phosphates with compost or composted did not increase significantly the total P accumulated in the plants. At pH 4.8 the application of composted TS increased the total P accumulated by the plants when compared with TS applied with or without the compost to the soil and all other treatments.